Pelatihan Pembuatan Desain Kemasan Produk Pada UKM Sari Ne Lemon - Ni Putu Desy Damayanthi; IGKG Puritan Wijaya ADH; Ni Nyoman Utami Januhari; I Made Surya Adi Putra; I Gusti Agung Indra Muliawan; I Putu Kusa Satrialandipa Putra; Komang Nova Triana Putra; I Made Bhaskara Gautama; I Nyoman Rudy Hendrawan; I Made Arya Budhi Saputra (Journal of Community Development, 2022)
Sari Ne Lemon in East Denpasar is an UKM that is active in lemon cultivation. The lemon plantation owned by Sari Ne Lemon is located in Pelaga Village, Petang District, Badung Regency. Although the lemon plantation is currently still in the village of Petang, the production and sales center is located in East Denpasar. Initially the results of the cultivation of lemon plantations were only in the form of lemons that had not undergone further processing. Currently, Sari Ne Lemon has developed lemon juice into packaged lemon juice. In its effort to develop lemon juice products, Sari Ne Lemon encountered difficulties in terms of packaging and marketing. The packaging owned by Sari Ne Lemon is still very simple, namely lemon juice is packaged and sold in plastic bottles. Therefore, the resulting product has not been able to compete in the industrial market. This service activity aims to find and implement solutions to the problems experienced by partners. Packaging that is only in the form of plastic bottles without labels will be changed into 2 types of packaging, namely labeled plastic bottle packaging and labeled plastic press glass packaging. With the activities of making branding and training on packaging of processed lemon juice products, it will produce products that have higher competitiveness and selling value. UKM Sari Ne Lemon has been helped by the successful development of their new product packaging through packaging design and implementation in 14 oz glass cups and small plastic bottles.